2023
DOI: 10.7759/cureus.37283
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Noncommunicable Disease Clinics in Improving Control of Hypertension and Diabetes Among Adults Residing in Rural Ballabgarh, Haryana

Abstract: High systolic blood pressure (SBP) and raised plasma glucose are major attributable and preventable causes of death worldwide. The objective of this study was to estimate the control rates and identify determinants of control of hypertension and diabetes among adults. MethodsA longitudinal follow-up study was conducted among all the adults registered at the noncommunicable disease (NCD) clinics under the national program at two primary health centers in Faridabad, Haryana. Data were collected every month from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…19 The control rates of both diabetes and hypertension are very poor owing to an increase in complications of these morbidities like stroke, myocardial infarction. 20 Many studies conducted among drivers have reported an increase in RTA incidence among drivers with hypertension and diabetes. [21][22][23] The present study showed that multimorbidity was associated with RTA.…”
Section: Discussionmentioning
confidence: 99%
“…19 The control rates of both diabetes and hypertension are very poor owing to an increase in complications of these morbidities like stroke, myocardial infarction. 20 Many studies conducted among drivers have reported an increase in RTA incidence among drivers with hypertension and diabetes. [21][22][23] The present study showed that multimorbidity was associated with RTA.…”
Section: Discussionmentioning
confidence: 99%